2016
DOI: 10.1016/j.toxrep.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic induced hematological and biochemical responses in nutritionally important catfish Clarias batrachus (L.)

Abstract: The impact of sublethal toxicity of sodium arsenite on hematological and certain biochemical parameters of the fresh water catfish Clarias batrachus has been analyzed following exposure of sublethal concentration (1 mg/L; 5% of LC50 value) of sodium arsenite for 10, 30, 45, and 60 days. Arsenic bioaccumulation in the blood tissue of the fish increased progressively with increased period of exposure. The values of total erythrocyte count (TECs), total leucocytes count (TLCs), hemoglobin concentration, and packe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…Arsenic-induced changes in MCV, MCH, and WBCs of current species were evident. Some other studies reported similar results with fluctuations in some fish such as Clarias batrachus, and Catla catla (Lavanya et al, 2011;Kumar and Banerjee, 2016).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Arsenic-induced changes in MCV, MCH, and WBCs of current species were evident. Some other studies reported similar results with fluctuations in some fish such as Clarias batrachus, and Catla catla (Lavanya et al, 2011;Kumar and Banerjee, 2016).…”
Section: Discussionsupporting
confidence: 66%
“…The liver is the major organ involved in the regulation of metabolic functions and most of the biotransformation of inorganic arsenic takes place in the liver (Kumar and Banerjee, 2016;Kumari et al, 2017). So, analysis of serum AST and ALT were widely used to demonstrate arsenic induced-hepatotoxicity (Dorcas and Solomon, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These changes possibly deteriorate the secretion of enzyme in the gut and absorption is also decreased due to damaged vili of intestine. This is also supported by the fi nding of Adewoyeso (2010); Kumar and Banerjee (2016) as they have observed depletion in glucose content in the fi sh Clarias garipinus.…”
Section: Introductionsupporting
confidence: 62%
“…Values are mean ± SE. As determined by Duncan's multiple range test, the other values of superscript were significantly different at 2 and 4 weeks (P < 0.05) by decreasing the oxygen supply due to red blood cell concentration and decreased hemoglobin (Kumar and Banerjee 2016). Hepatosomatic index is used as an important indicator of health status in aquatic animals manifesting the toxic effects of metal exposure (Datta et al 2007;Bolger and Connolly 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma glucose is a reliable indicator of multiple stress factors in fish, including heavy metals, and is commonly increased by carbohydrate metabolism (CiCiK and ENGiN 2005). The increase in glucose level is attributed to the breakdown of proteins and high-density lipids, resulting in the release of carbohydrates, and decreased lipid and protein levels, following metal toxicity (Kumar and Banerjee 2016). Plasma cortisol levels are widely used in the primary response to stressors such as metals and insecticides; cortisol and other corticosteroid hormones maintain homeostasis under toxicity (Fırat et al 2011).…”
Section: Discussionmentioning
confidence: 99%